The paintings of Korean Shaman Gods : history, relevance and role as religious icons - Kim, Tʻae-gon, 1937- (Renaissance books Korean literature series ;, 2018)
This is the first monograph on the subject to be published in English. It comprises 130 full-colour plates of shaman gods. Supported by two introductory chapters 'Reflections on Shaman God Paintings and Shamanism' by Kim Tae-gon, and 'The Shaman God Paintings as an Icon and Its Artistic Qualities'.